Arabic language as the foundation of semitic languages - Yaacob, Solehah@Nik Najah Fadilah (Arab Society of English Language Studies, 2014)
There is a view that there was a hidden Greek transmission into Arabic linguistics and terminology which was subsequently borrowed by traditional Arab scholars who started to describe their own language scientifically. This has been rejected by some Muslim scholars who believe that the purity of Arabic linguistics, such as the theory of Arabic syntax, is totally free from any foreign influence. Thus, the purpose of the research is to discover the origin of the Arabic language before the dawn of Islam. The research focuses on the linguistic corpus development in order to give a balanced judgment.